A study on relationship between working capital and profitability - Hassan Ghodrati; Jaber Ghanbari (Management Science Letters)
This paper studies the relationship between working capital management and profitability of accepted corporations in Tehran Stock Exchange over the period 2008-2012. The study selected 66 firms as a statistical sample based on Cochran formula and simple random selection. In this study, variables including the average period of collecting accordance, periods of circulation of inventories, the average period of debt payment, and cycle of cash conversion on the factories operating profits are studied. The research method is applied and collection of data is solidarity, the Pierson and Regression solidarity are used. Results show that variables of capital investment management and profitability were in opposite direction. If the period of collecting accordance, period of debt payment, period of circulation of inventories and the cycle of cash conversion increase, it decreases the period profitability and the manager can decrease the period of debt payment, period of cash conversion to the least amount of positive value for affiliate.